AI-Driven HRM and Employee Performance: The Mediating Role of HR Agility in Industrial Companies - Ade Mubarok; Nursaimatussaddiya Nursaimatussaddiya (CV. Sakura Digital Nusantara, 2026)
Purpose - This study examines the effect of AI-driven human resource management on employee performance and investigates the mediating role of HR agility in industrial companies in West Java, Indonesia. Design/methodology/approach – A quantitative explanatory design was employed using a cross-sectional survey of 214 employees from industrial firms. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS to test both direct and indirect relationships among the constructs. Findings – The results indicate that AI-driven human resource management has a positive and significant effect on HR agility and employee performance. HR agility also significantly improves employee performance. Furthermore, HR agility partially mediates the relationship between AI-driven human resource management and employee performance, indicating that the effectiveness of AI-based HR practices depends on the organization’s ability to develop adaptive and responsive HR systems. Limitations – This study is limited by its cross-sectional design, reliance on self-reported data, and focus on industrial companies in a single regional context, which may restrict generalizability. Originality/value – This study contributes to digital HRM and dynamic capability literature by positioning HR agility as a key mechanism through which AI-driven HR practices enhance employee performance in an emerging economy context.